1995
DOI: 10.1038/sc.1995.126
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Wheelchair User's Shoulder Pain Index (WUSPI)

Abstract: Many long term wheelchair users develop shoulder pain. The purpose of this study was to examine the reliability and validity of the Wheelchair User's Shoulder Pain Index (WUSPI), an instrument which measures shoulder pain associated with the functional activities of wheelchair users. This 15-item functional index was developed to assess shoulder pain during transfers, self care, wheelchair mobility and general activities. To establish test-retest reliability, the index was administered twice in the same day to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
114
3
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 2 publications
0
114
3
4
Order By: Relevance
“…Prior to analysis the intra-rater, interrater reliability, speci®city and face validity of the measures were tested in a Pilot Study undertaken with a sample of 10 persons with paraplegia in the inpatient facility at the Burwood SIU. The results were analyzed in view of the extensive analysis of the psychometric properties undertaken on the WUSPI 23 and MFA. 24 This pre-testing of the instruments also assisted with determining the functional relevance, language difficulties and completion time.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to analysis the intra-rater, interrater reliability, speci®city and face validity of the measures were tested in a Pilot Study undertaken with a sample of 10 persons with paraplegia in the inpatient facility at the Burwood SIU. The results were analyzed in view of the extensive analysis of the psychometric properties undertaken on the WUSPI 23 and MFA. 24 This pre-testing of the instruments also assisted with determining the functional relevance, language difficulties and completion time.…”
Section: Methodsmentioning
confidence: 99%
“…12, 13 Subbarao et al 14 in comparing individuals with SCI who were either with or without shoulder pain, reported that time from SCI onset was the only variable that di erentiated the two groups. Curtis et al 15,16 reported a strong relationship between age and the Wheelchair User's Shoulder Pain Index (WUSPI) score and a somewhat weaker relationship between years of wheelchair use and the WUSPI score. Although shoulder pain prevalence increases with age and years of wheelchair use, the age of the individual with SCI had the greater in¯uence, particularly among extremely young or older subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Although shoulder pain prevalence increases with age and years of wheelchair use, the age of the individual with SCI had the greater in¯uence, particularly among extremely young or older subjects. 16 Gellman et al 6 in an UE evaluation of 84 individuals with paraplegia reported that shoulder pain frequency during transfers increased with the length of time from SCI onset with Interface between subject-wheelchair Seelen and Vuurman 17 reported that the complex sensorimotor impairments associated with SCI limit the dynamic control of sitting posture and task performance while sitting, likely serving as the precursor to the development of compensatory UE and trunk motor control mechanisms. Hobson et al 18 reported that decreased trunk stability necessitated individuals with paraplegia to assume a biomechanically abnormal sitting posture characterized by a`C' shaped thoracic spine kyphosis, an extended cervical spine, a¯attened lumbar spine, and a posteriorly tilted pelvis (approximately 158 more tilt than non-impaired subjects).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations